Epidemiology and etiology of influenza-like-illness in households in Vietnam; it’s not all about the kids! - Nguyen, D; Mai, L; Bryant, J; Hang, N; Hoa, L; Nadjm, B; Thai, P; Duong, T; Anh, D; Horby, P; van Doorn, H; Wertheim, H; et al. (Elsevier, 2016)
Background Household studies provide opportunities to understand influenza-like-illness (ILI) transmission, but data from (sub)tropical developing countries are scarce. Objective To determine the viral etiology and epidemiology of ILI in households. Study design ILI was detected by active case finding amongst a cohort of 263 northern Vietnam households between 2008 and 2013. Health workers collected nose and throat swabs for virus detection by multiplex real-time RT-PCR. Results ILI was detected at least once in 219 (23.7%) of 945 household members. 271 (62.3%) of 435 nose/throat swabs were positive for at least one of the 15 viruses tested. Six viruses predominated amongst positive swabs: Rhinovirus (28%), Influenza virus (17%), Coronavirus (8%), Enterovirus (5%), Respiratory syncytial virus (3%), Metapneumovirus virus (2.5%) and Parainfluenza virus 3 (1.8%). There was no clear seasonality, but 78% of episodes occurred in Winter/Spring for Influenza compared to 32% for Rhinovirus. Participants, on average, suffered 0.49 ILI, and 0.29 virus-positive ILI episodes, with no significant effects of gender, age, or household size. In contrast to US and Australian community studies, the frequency of ILI decreased as the number of household members aged below 5 years increased (p = 0.006). Conclusion The findings indicate the need for tailored ILI control strategies, and for better understanding of how local childcare practices and seasonality may influence transmission and the role of children.